Der stille Kommanditist in der Publikums-KG Die Dogmatik der qualifizierten Treuhand, ihr Haftungsregime und Auskunftsansprüche - Dogan, Sait (Studien zum Handels-, Arbeits- und Wirtschaftsrecht, 2021)
The thesis examines the qualified trust in public limited partnerships with particular regards to general trust and association law. In doing so, the author comes to the conclusion that this legal figure actually conceals the historically not newly invented figure of the silent limited partner - the beneficiary becomes a genuine internal partner in the external association. Based on this, the practice-relevant areas of liability and claims for information about their identity are examined, whereby the author often arrives at innovative approaches. The work thus makes a valuable contribution to the treatment of qualified trusts in science and practice. The author worked as a research associate in capital market and investment law.